Strategi Work-Life Balance Human Capital Dalam Meningkatkan Kinerja Perusahaan Yang Berkerlanjutan - Kusumaningrum, Hesti; -, Cinta Pradana Putri; Fitri, Naya Aranti (Cendekia : Jurnal Pendidikan dan Keagamaan, 2024)
This article reviews the importance of human capital management strategies, especially in the context of recruiting, developing and retaining talented employees. Through training and development programs, companies are able to expand employees' skills and knowledge for greater contributions. In addition, the implementation of work-life balance is also an important part of the human capital strategy, where providing work flexibility to employees can promote happiness and productivity, which in turn affects the appearance of the company as a totality. The research method used is a literature review to identify theoretical contributions, theories, and methodologies related to this topic. As such, this article provides a brief but clear overview of sustainable human capital strategies.